Anemia during pregnancy and its influence on postpartum hemorrhage - Syamsuriyati, Syamsuriyati; Handayani, Rika; Suhartono, Sunartono; Syarif, Sutriani; Triananinsi, Nurhidayat (Universitas Muhammadiyah Purwokerto, 2024)
Background: Up to 50% of pregnant women in low-income and middle-income countries are affected by anemia, and 30.43% of maternal deaths in Indonesia occur during the postpartum period. One of the predisposing factors for postpartum hemorrhage is anemia in pregnancy.Purpose: To investigate the experience of anemia during pregnancy and its influence on a postpartum hemorrhage.Method: This is an observational analysis with a case-control study design. A total of 30 postpartum mothers took part in this research (15 case groups and 15 control groups). The anemia during pregnancy and incident of postpartum hemorrhage observed—data analysis with chi-square.Results: As many as 76.5% of mothers who were anemic during pregnancy experienced postpartum hemorrhage. The analysis results found that anemia during pregnancy had a significant effect on the incidence of postpartum hemorrhage (p<0.001).Conclusions: Anemia during pregnancy is very dangerous for postpartum mothers because it can have an impact on a hemorrhage.